2001
DOI: 10.1002/syn.1072
|View full text |Cite
|
Sign up to set email alerts
|

Anticocaine catalytic antibodies have no affinity for RTI compounds: Implications for treatment

Abstract: Potential medications for cocaine abusers include: anticocaine catalytic antibodies, which could serve as circulating peripheral blockers of cocaine that prevents its action in the brain; and 3-phenyltropane cocaine analogs, which could serve as potent, selective, and long-lasting substitutes that reduce drug-seeking. In order to evaluate the compatibility of these agents, we measured if a catalytic antibody would bind and interact with some cocaine analogs. Anticocaine catalytic antibody 15A10 had no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Our study suggests that women in Mbale District have the perceived stigma of HIV/AIDS as described by Bharat et al[ 29 ]. The perceived stigma of HIV/AIDS is informed by enacted stigma in the society usually in the form of gossip, blame, avoidance of physical contact, discrimination, neglect and rejection.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our study suggests that women in Mbale District have the perceived stigma of HIV/AIDS as described by Bharat et al[ 29 ]. The perceived stigma of HIV/AIDS is informed by enacted stigma in the society usually in the form of gossip, blame, avoidance of physical contact, discrimination, neglect and rejection.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, the stigma related to HIV/AIDS is often superimposed on pre-existing stigmas of affected people[ 27 ]. Bharat et al[ 29 ] have identified three different types of HIV/AIDS stigma namely:…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic antagonism of cocaine could be implemented by administration of a molecule, such as an anti-cocaine antibody, which binds tightly to cocaine so as to prevent cocaine from crossing the blood−brain barrier . A more potent blocking action could also be implemented by administration of a more stoichiometric agent such as a catalytic antibody, an artificial enzyme, that not only binds but also degrades cocaine and thereby frees itself for further binding. ,, To further the development of catalytic antibodies for hydrolysis of cocaine, , we sought to understand the mechanism underlying hydrolysis by natural cocaine esterases. Also, natural esterases could themselves be useful therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Anticocaine catalytic antibodies, which serve as circulating peripheral blockers of cocaine that prevent its action in the brain, provide an alternative medication for cocaine abuse. , We found that several 3-phenyltropane analogues did not possess affinity for the anticocaine catalytic antibody 15A10, suggesting that the two types of treatments could be used together …”
Section: (1) Monoamine Transporters As Target For Addiction Therapymentioning
confidence: 88%
“…13,71 We found that several 3-phenyltropane analogues did not possess affinity for the anticocaine catalytic antibody 15A10, suggesting that the two types of treatments could be used together. 72 Thus, the 3-phenyltropane analogues could give the benefits associated with the substitution therapy, while the antibody would simultaneously reduce the effects of cocaine in the event of a relapse.…”
mentioning
confidence: 99%